Bioinformatic and in vitro Analyses of Arabidopsis Starch Synthase 2 Reveal Post-translational Regulatory Mechanisms - Patterson, Jenelle A.; Tetlow, Ian J.; Emes, Michael J. (Frontiers in Plant Science, 2018)
Starch synthase 2 (SS2) is an important enzyme in leaf starch synthesis, elongating intermediate-length glucan chains. Loss of SS2 results in a distorted starch granule phenotype and altered physiochemical properties, highlighting its importance in starch biosynthesis, however, the post-translational regulation of SS2 is poorly understood. In this study, a combination of bioinformatic and in vitro analysis of recombinant SS2 was used to identify and characterize SS2 post-translational regulatory mechanisms. The SS2 N-terminal region, comprising the first 185 amino acids of the mature protein sequence, was shown to be highly variable between species, and was predicted to be intrinsically disordered. Intrinsic disorder in proteins is often correlated with protein phosphorylation and protein-protein interactions. Recombinant Arabidopsis thaliana SS2 formed homodimers that required the N-terminal region, but N-terminal peptides could not form stable homodimers alone. Recombinant SS2 was shown to be phosphorylated by chloroplast protein kinases and recombinant casein kinase II at two N-terminal serine residues (S63, S65), but mutation of these phosphorylation sites (Ser>Ala) revealed that they are not required for homo-dimerization. Heteromeric enzyme complex (HEC) formation between SS2 and SBE2.2 was shown to be ATP-dependent. However, SS2 homo-dimerization and protein phosphorylation are not required for its interaction with SBE2.2, as truncation of the SS2 N-terminus did not disrupt ATP-dependent HEC assembly. SS2 phosphorylation had no affect on its catalytic activity. Intriguingly, the removal of the N-terminal region of SS2 resulted in a 47-fold increase in its activity. As N-terminal truncation disrupted dimerization, this suggests that SS2 is more active when monomeric, and that transitions between oligomeric state may be a mechanism for SS2 regulation.